Application of the direct method for cohesive law estimation applied to the strength prediction of double-lap joints - Carvalho, U.T.F (2016)
Currently, significant efforts are being made in the design of aircraft and aeronautical applications to reduce weight and improve reliability. Thus, adhesive bonding techniques have been largely employed, which also enables the combined use of steel with lighter materials such as aluminium or high strength composites. Cohesive Zone Models (CZM) are a powerful tool for the design of bonded structures, but they require careful estimation of the cohesive laws for reliable results. This work experimentally evaluates by the J-integral/direct method the tensile and shear CZM laws of three adhesives with distinct ductility. The Double-Cantilever Beam (DCB) and End-Notched Flexure (ENF) specimens were considered to obtain the tensile and shear CZM laws of the adhesives, respectively. After obtaining the tensile and shear CZM laws, triangular, exponential and trapezoidal CZM laws were built to reproduce their behaviour. Validation of these CZM laws was undertaken with a mixed-mode geometry (double-lap joint) considering the same three adhesives and varying overlap lengths (LO). The strength prediction by this technique revealed accurate predictions for a given CZM law shape, depending on the adhesive ductility, although all CZM law shapes were moderately accurate.